Structural Analysis of Readiness of the Future Primary School Teacher to the Formation of Social Competence of Primary School Children - Yurchenko, Oksana (Pedagogical Discourse, 2016)
The article defines the essence of the concept of «readiness of future primary school teacher to the formation of social competence of primary school children», based on the analyses of scientific literature. The analysis made it possible to conclude that the researched concept should be interpreted as the component personal formation of a future teacher, combining in the structure the motives of professional activity, social intelligence of a future teacher, system of knowledge and skills of primary school children socialization and their formation as active subjects of social reality, and ensures its ability to successfully develop the social competence of students in their future professional activity. According to the conducted scientific research the structure of readiness of the future primary school teacher to the formation of social competence of primary school children in the form of motivational, cognitive, activity and personal components was summarized. It was proved that in order to make objective diagnosing of formation of future primary school teacher readiness to the formation of social competence of primary school children it is necessary to use certain criteria of evaluation the components of the studied characteristics: motivational component – value-motivational criteria, cognitive component – knowledge and information criteria, activity component – operational and active, personal component - personal and social development criteria. The system of indicators of readiness formation of future primary school teacher to forming the social competence primary school children according to determined criteria was generalized. The study offers to assess the formation of future primary school teacher readiness to forming the social competence of primary school children according to the following levels: high (professional and active), sufficient (efficient and productive), average (situational and search), low (reproductive and partial). The conducted study gives an opportunity to do the experimental verification of readiness formation of future primary school teachers. Key words: readiness to activity, readiness of future primary school teacher to the formation of social competence of primary school children, the structure of readiness.